1984
DOI: 10.1113/jphysiol.1984.sp015249
|View full text |Cite
|
Sign up to set email alerts
|

Slow excitatory synaptic potentials recorded from neurones of guinea‐pig submucous plexus.

Abstract: SUMMARY1. Intracellular recordings made from neurones of guinea-pig submucous plexus revealed three types of synaptic input: cholinergic excitatory synaptic potentials (fast e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
104
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 31 publications
16
104
0
Order By: Relevance
“…These are more rapid in onset and decay, lasting 10 -30 s, and may be due to an increase in non-specific cation conductance [134]. This latter conclusion is controversial as some authors have reported slow EPSPs of this type associated with small decreases in membrane conductance, rather than the increases implied by this conclusion [7,93,117,125]. The third class of slow EPSP has been termed "sustained slow postsynaptic excitation" and is evoked by prolonged trains of relatively low frequency stimulation [2,25].…”
Section: Slow Epsps Their Underlying Conductances and Their Transmitmentioning
confidence: 59%
See 1 more Smart Citation
“…These are more rapid in onset and decay, lasting 10 -30 s, and may be due to an increase in non-specific cation conductance [134]. This latter conclusion is controversial as some authors have reported slow EPSPs of this type associated with small decreases in membrane conductance, rather than the increases implied by this conclusion [7,93,117,125]. The third class of slow EPSP has been termed "sustained slow postsynaptic excitation" and is evoked by prolonged trains of relatively low frequency stimulation [2,25].…”
Section: Slow Epsps Their Underlying Conductances and Their Transmitmentioning
confidence: 59%
“…Second, there have been many reports that slow EPSPs in S/uniaxonal myenteric neurons can involve reductions in K + conductance or increased neuronal input resistance [15,43,59,93,125]. Third, many slow EPSPs in submucosal S/uniaxonal neurons are associated with increased input resistance and reverse at about the K + equilibrium potential [7,117]. Indeed, it has been reported that both conductance increase and conductance decrease slow EPSPs are seen in the same submucosal neurons [51].…”
Section: Slow Epsps Their Underlying Conductances and Their Transmitmentioning
confidence: 99%
“…Submucosal plexus preparations were obtained from the small intestine of guinea-pigs (150-250 g); methods of tissue preparation and intracellular recording from submucosal neurones were as detailed previously (Surprenant, 1984). Tissues were superfused at 3-4 ml min-' with a physiological solution of the following composition (mM): NaCl 126, NaH2PO4 1.2, MgCl2 1.2, CaCl2 2.5, KCl 5, NaHCO3 25, glucose l1; gassed with 95% 02 and 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…The stimulus threshold for activation of the nicotinic e.p.s.p. is much lower than for activation of the adrenergic inhibitory synaptic potential or the peptidergic slow excitatory synaptic potential (Surprenant, 1984); in all these experiments stimulus parameters were used which elicited only the nicotinic e.p.s.p. The time course of decay of the e.p.s.p.…”
Section: Methodsmentioning
confidence: 99%
“…Methods of dissection, intracellular recording from submucosal neurones, stimulation of interganglionic nerve fibres and optical measurements of arteriolar diameter have been described in detail previously (Surprenant, 1984;Neild et al, 1990 Ltd, 1990 nist; previous studies have shown that cumulative and noncumulative applications of UK 14304 produce similar hyperpolarizations in submucosal neurones (North & Surprenant, 1985;Surprenant & North, 1988). Schild plots were obtained from data on individual neurones and the dissociation equilibrium constants (KDs) and slopes so obtained were then averaged.…”
Section: Methodsmentioning
confidence: 99%